Host induced gene silencing of Magnaporthe oryzae by targeting pathogenicity and development genes to control rice blast disease - Wang, Mengying; Dean, Ralph A. (Frontiers in Plant Science, 2022)
Rice blast disease caused by the hemi-biotrophic fungus Magnaporthe oryzae is the most destructive disease of rice world-wide. Traditional disease resistance strategies for the control of rice blast disease have not proved durable. HIGS (host induced gene silencing) is being developed as an alternative strategy. Six genes (CRZ1, PMC1, MAGB, LHS1, CYP51A, CYP51B) that play important roles in pathogenicity and development of M. oryzae were chosen for HIGS. HIGS vectors were transformed into rice calli through Agrobacterium-mediated transformation and T0, T1 and T2 generations of transgenic rice plants were generated. Except for PMC1 and LHS1, HIGS transgenic rice plants challenged with M. oryzae showed significantly reduced disease compared with non-silenced control plants. Following infection with M. oryzae of HIGS transgenic plants, expression levels of target genes were reduced as demonstrated by Quantitative RT-PCR. In addition, treating M. oryzae with small RNA derived from the target genes inhibited fungal growth. These findings suggest RNA silencing signals can be transferred from host to an invasive fungus and that HIGS has potential to generate resistant rice against M. oryzae.